CORPORATE SOCIAL RESPONSIBILITY IN SRI LANKA: THE IMPACT OF GOVERNMENT INFLUENCE, SOCIETAL EXPECTATIONS AND THE 2004 TSUNAMI - Dharmaratne, Tilina; Christopher, Theo; Cullen, Lisa (The journal of contemporary issues in business and government, 2011)
This study examines government influence, changes in societal expectations and the 2004 tsunami on corporate social responsibility (CSR) in Sri Lanka, a developing country. Hypotheses are formulated based on legitimacy theory to examine the annual changes in total quantity and categories of CSR disclosures between 2004 and 2007. Four directional hypotheses are used to test the increase in CSR disclosures and the increase in category-specific CSR disclosures based on a disclosure classification system. A null hypothesis is used to test whether the change in CSR disclosures from 2004 to 2005 and from 2005 to 2006 remained relatively constant after 2006. The directional hypotheses and the null hypothesis on the extent of disclosure are supported but the category-specific hypotheses are rejected. This result provides support for legitimacy theory.